Addiction and grace : love and spirituality in the healing of addictions - May, Gerald G. frey50 (San Francisco, CA : HarperOne, 2006)
"Drawing on his experience as a psychiatrist working with the chemically dependent, May emphasizes how addiction represents a doomed attempt to assert complete control over our lives. 'Addiction & Grace' is a compassionate and wise treatment of this important topic, offering a critical yet hopeful guide to a place of freedom based on contemplative spirituality. This 'Plus' edition includes two additional essays by Gerald May not included in the hardcover version" --Cover, p. 4.
Desire: addiction and human freedom -- Experience: the qualities of addiction -- Mind: the psychological nature of addiction -- Body: the neurological nature of addiction -- Spirit: the theological nature of addiction -- Grace: the qualities of mercy -- Empowerment: grace and will in overcoming addiction -- Homecoming: discernment and the consecrated life -- Notes -- Index -- PLUS: Lightness of soul. The dark night of recovery.
Includes Plus: insights, interviews and more with two additional articles: Lightness of the soul (1991) and The dark night of recovery (2005).
Originally published in 1988.
Keywords: Compulsive behavior -- Religious aspects -- Christianity; Substance abuse -- Religious aspects -- Christianity; Christianity; Compulsive Behavior; Substance-Related Disorders